Perjuangan Tokoh Perempuan Dalam Antologi Cerpen Tiga Paragraf Sekian Jalan Menuju Pasar Karya Kampung Pentigraf Indonesia - Febi Erika Putri; Tri Indrayanti (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This study aims to determine the forms of struggle of female characters in the three-paragraph short story anthology the Way to Market by Indonesian Pentigraf Village. This study uses a descriptive qualitative method with a feminist literary approach. Broadly speaking, feminism is a women's liberation movement. Feminism has several streams, including radical feminism, liberal feminism, Marxist feminism, and socialist feminism. In accordance with the problem to be studied, the theory used is the theory of socialist feminism. Collecting data in this study using documentation techniques and library techniques. The data analysis technique in this study was as follows: reading the entire collection of short stories in the three-paragraph short story anthology That's All the Way to Market by Indonesian Pentigraf Village, marking short story titles related to the problem in research, Re-reading selected short stories, marking the quotations quotes that contain the meaning of the struggle of a woman in the family. After that draw conclusions. The results of this study are as follows: the form of struggle of female figures within the family sphere according to their role as a mother, wife and child. By using the theory of socialist feminism, it can be seen what forms a woman's struggle is seen from her role in the family to create a harmonious family.